2023
DOI: 10.3390/ijpb14020037
|View full text |Cite
|
Sign up to set email alerts
|

Response of Phenolic Compounds in Lippia graveolens Kunth Irrigated with Aquaculture Wastewater and Steiner Solution

María Isabel Nieto-Ramírez,
Ana Angélica Feregrino-Pérez,
Humberto Aguirre Becerra
et al.

Abstract: Lippia graveolens is one of the most important aromatic species in Mexico due to antioxidant and antibiotic activities reported in its essential oil. The aim of this work was to assess the effect of irrigation with aquaculture wastewater and salicylic acid addition on the production of phenolic compounds in L. graveolens. L. graveolens plants (14) were irrigated with aquaculture wastewater and (14) using Steiner solution for 28 days; at the same time, salicylic acid was exogenously applied at 0.0 (control), 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Regarding the increase in total phenolic compounds due to the N content provided in the irrigation water, different behaviors have been described in the literature. Authors such as Nieto-Ramírez et al [31] observed a higher content in L. graveolens irrigated with aquaculture wastewater than in those irrigated with a Steiner solution. Similar results were also observed in Origanum vulgare L. ssp.…”
Section: Total Phenolic Compounds and Antioxidant Activity (Abts + *)mentioning
confidence: 95%
“…Regarding the increase in total phenolic compounds due to the N content provided in the irrigation water, different behaviors have been described in the literature. Authors such as Nieto-Ramírez et al [31] observed a higher content in L. graveolens irrigated with aquaculture wastewater than in those irrigated with a Steiner solution. Similar results were also observed in Origanum vulgare L. ssp.…”
Section: Total Phenolic Compounds and Antioxidant Activity (Abts + *)mentioning
confidence: 95%